2014
DOI: 10.1161/strokeaha.113.002629
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Not Volume of Bleeding Predicts Angiographic Vasospasm in Nonaneurysmal Subarachnoid Hemorrhage

Abstract: Variables were compared using χ 2 or Mann-Whitney tests. Correlation coefficients were calculated for the association of blood burden and quantitative degree of vasospasm. Odds ratios for rate of outcomes in those with diffuse versus PM-SAH were calculated using logistic regression modeling, after adjustment for covariates, specifically blood burden and established predictors (ie, age and World Federation of Neurosurgical Societies grade).Background and Purpose-Spontaneous idiopathic subarachnoid hemorrhage (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 15 publications
(22 reference statements)
0
16
1
Order By: Relevance
“…In other words, it may be that there is not anything inherent to the pathophysiology of diffuse pattern bleeding that leads to a higher incidence of hydrocephalus, aside from the effects of greater blood volume. This is in contrast to our prior work in vasospasm and NA-SAH, which demonstrated that pattern was an independent predictor of angiographic vasospasm, even when accounting for blood burden [10]. Interestingly, when we evaluated the progression of acute to chronic hydrocephalus, we found that diffuse bleeding pattern did remain an independent predictor of shunting.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In other words, it may be that there is not anything inherent to the pathophysiology of diffuse pattern bleeding that leads to a higher incidence of hydrocephalus, aside from the effects of greater blood volume. This is in contrast to our prior work in vasospasm and NA-SAH, which demonstrated that pattern was an independent predictor of angiographic vasospasm, even when accounting for blood burden [10]. Interestingly, when we evaluated the progression of acute to chronic hydrocephalus, we found that diffuse bleeding pattern did remain an independent predictor of shunting.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to aneurysmal SAH, it is thought that NA-SAH represents a more benign entity with less morbidity and mortality, especially in the context of a perimesencephalic SAH (PM-SAH) pattern of bleeding [2][3][4][5][6]. Recent studies, however, have questioned whether risk of complications such as vasospasm or hydrocephalus after NA-SAH is actually minimal, especially for those with a diffuse, aneurysmal-like pattern of bleeding [7][8][9][10]. It remains unclear whether this variability in clinical course is explained by differing pathophysiologic processes underlying these two types of bleeding, or simply mediated by the fact that those with diffuse bleeding tend to harbor more cisternal and intraventricular blood.…”
Section: Introductionmentioning
confidence: 99%
“…Kramer et al (12) found that the clinical performance of the modified scale is better. Hijdra et al (8) developed a more comprehensive grading scale that is superior to the modified (16). Although due to the earlier time period of the data collection we could not test the newer scales, our results support the necessity of reevaluation of the original Fisher grading scale.…”
Section: Amount and Location Of Bloodmentioning
confidence: 52%
“…49 The isolated perimesencephalic pattern has a better prognosis than other subtypes of SAH, with hydrocephalus and symptomatic vasospasm being decidedly uncommon on follow-up. 45,50 Although the cause of pSAH remains elusive, multiple studies have suggested a venous origin for a majority of pSAH cases. Because 10% of posterior circulation aneurysms present with a perimesencephalic bleeding pattern, some angiographic imaging is essential, but the use of additional angiographic studies is debated.…”
Section: Discussionmentioning
confidence: 99%
“…Vasospasm and hydrocephalus are infrequent with pSAH. 45,50 Given the excellent sensitivity and the noninvasive nature of CTA, repeat imaging may be performed preferentially using CTA. 74 by guest on May 9, 2018 http://stroke.ahajournals.org/ Downloaded from…”
Section: Discussionmentioning
confidence: 99%